Si può costruire il concetto di periodicità senza il modello atomico di Bohr? - Chillura Martino, Delia; Lombardo, Renato; Maggio, Antonella; Rizzo, Matteo; Vivona, Gaspare (Chimica nella Scuola, 2022)
The concepts of atom, element, and substance, while constituting fundamental chemical concepts, are generally tricky to understand. The not authentic comprehension of these concepts results in their not appropriate use, in the association of the idea of periodicity almost exclusively with the description of the atomic properties and the consequent limited use of the periodic table. Based on this evidence, we investigated the possibility of presenting periodicity’s concept without introducing atomic models and electronic configurations, while referring exclusively to the classification criteria of the elements identified by Mendeleev. As a result, a module of a vertical path aimed at developing the concept of periodicity was designed. Furthermore, we planned and realized activities based on the macroscopic properties and composition of substances, which made it possible to obtain a first simple Periodic Table of elements. The project was proposed and carried out as part of a Master’s thesis in Didactics of Chemistry. This contribution will discuss the choice of the methodology, the strategy, and the tools employed in these activities.